PENGARUH PARTISIPASI ANGGARAN, KOMITMEN ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA MANAJERIAL (Survei Pada Perusahaan Manufaktur di Kawasan Industri Pulogadung) - Waribu, Leni; Tarmizi, M. Irfan (Jurnal Akuntansi AKTIVA, 2025)
This research aims to determine the influence of budget participation, organizational commitment, and work motivation on managerial performance. This research was conducted at a manufacturing company in the Pulogadung Industrial Area, using quantitative methods and primary data sources collected through questionnaires. This research applies non-probability sampling techniques with convenience sampling and the Likert scale as the measurement scale. The results of the questionnaire were distributed to 70 respondents and analyzed using the IBM SPSS Statistics 30 software. The results of this research show that these three variables have a positive and significant effect on managerial performance, both partially and simultaneously.